Uma extensão da visão estrutural do NCL Composer para integração de código imperativo - Ferreira, Thales Pordeus (2014)
NCL application requirements such as the need for dynamic content processing, makes their development challenge. These applications are defined with a declarative part and additionally a portion imperative that relates the media objects to a operation processing complex (for example, a programmed logic described in a script language Lua). Within the development of NCL applications, an option taken by the authors of the document is to use the structural view of the NCL Composer to relate visually the media objects with media objects imperatives. Currently, despite the NCL Composer support the relationship with the media objects imperatives, it is possible to identify an inefficiency associated to integrate fast and simple imperative code in an application NCL. The objective of this work is to propose an extension to the structural view that better integrate media objects and imperative code, in order to decrease the time to use the content in this media imperative. The paper presents an evaluation of the impact on productivity of application development compatible with the specification Ginga-NCL.